Guide to research projects for engineering students planning, writing and presenting - Leong, Eng-Choon; Heah, Carmel Lee Hsia; Ong, Kenneth Keng Wee (CRC Press Taylor & Francis, 2015)
"Are you a student facing your first serious research project? If you are, it is likely that you'll be, firstly, overwhelmed by the magnitude of the task, and secondly, lost as to how to go about it. What you really need is a guide to walk you through all aspects of the research project, from planning and conducting your research project to writing and presenting it. Guide to Research Projects for Engineering Students: Planning, Writing and Presenting is the guide you need to do the job efficiently. Specifically Designed with Engineering and Technical Science Students in Mind The book is organized into three sections, broken down into concise chapters that focus on a specific topic and the skills required. The section on planning shows you how to choose a project, research a topic, write a project proposal, plan the project, select methods and methodologies, and keep records. The section on writing provides help on writing the different sections of a research report as well as introduces you to the strategies and language conventions required for writing an effective research report. Finally, the section on presenting covers creating effective figures and layout, preparing for a project presentation, and the dos and don'ts in delivering a presentation. Advice on how to use IT tools effectively is given throughout the book."--Publisher's website